Translation, politics, and development: A corpus-based approach to evaluating China’s development aid discourse - Tekwa, Kizito; Li, Mei (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
China’s rise to global prominence has been coupled with a development aid approach and narrative that contradicts long-standing Western-oriented models and discourses. Despite the existence of tangible development projects that bear testimony to Chinese aid to developing countries and which clearly espouse the principles upon which the aid is founded, critics continue to allege that the aid is a façade that enables China to advance its political ideology and vision. Using a corpus-based approach, we investigated the extent to which China’s political discourse finds its way into the development aid discourse either by senior party officials or through a government-managed collaborative translation mechanism. To do so, we designed a monolingual corpus of the speeches of top-ranking CPC party officials presented at party-organized events and bilingual (Chinese–English) corpora of the discourse used by Chinese government officials during development aid exchanges. We extracted political terms, based mostly on their frequency of use, from the monolingual corpus and verified the extent of their presence in the bilingual corpora of the development aid discourse. Furthermore, we studied the terms and their contexts of use in the bilingual corpora to determine whether translation served as a medium through which China’s political discourse was possibly being introduced into its development aid discourse. Our investigation led us to conclude that China’s development aid discourse contains an insignificant amount of political terminology mirroring China’s own development path. We also concluded that translation did not constitute, in any tangible way, a means by which the presence of China’s political discourse in its development aid discourse could be enhanced. However, we uncovered issues related to terminology management, literal translation, and machine translation which suggest that China was struggling to cope with preserving source text and, presumably, target text linguistic and cultural elements, while taking advantage of current advances in translation technology. We propose both structural and translational modifications that could help China curb anti-development aid criticism while enhancing its development aid discourse.